A Rare Congenital Perineal Groove - Enyew Abate (Hindawi Limited, 2022)
Background. Perineal groove is a rare congenital anomaly characterized by nonepithelialized mucous membrane that appears as an erythematous sulcus in the perineal midline, extending from the posterior vaginal fourchette to the anterior anal orifice. It is one of the uncommon anomalies of anogenital region that is unknown to many clinicians, and it is usually misdiagnosed as an anal fissure, perineal trauma, diaper dermatitis, infection, or sexual abuse. Case Presentation. Seven-day-old female neonate was brought by her parents after they observe reddish discoloration of her genitalia. Upon examination, there was a vertical perineal wet groove-like unkeratinized erythematous lesion with no bleeding, sign of infection, or inflammation that extends from the posterior vaginal fourchette to the anal rim. The newborn was sent home after counseling with a reassessment plan in case of complications. Conclusions. Recognition of the congenital perineal groove at birth is important for the health care providers to deliver an appropriate parental counseling and appropriate follow-up.